👤

Bonjour, je souhaiterai obtenir de l'aide pour dm pour demain !

Soit f ( x ) = (x-3)²-2(x-3)(2-5x).

Developper.
Factoriser.
Résoudre pour f (x) = 0

Merci !


Répondre :

salut,

*Developper :
 f (x) = (x-3)²-2(x-3)(2-5x)
=x²-6x+9 -2(2x-5x²-6+15x)
= x² -6x + 9 -4x + 10x² +12 -30x
= 11x² -40 x +21

*Factoriser :
f (x) = (x-3)²-2(x-3)(2-5x)
= (x-3) [(x-3) -2(2-5x)]
= (x-3) (x-3-4+10x)
= (x-3) (11x -7)

*Résoudre pour f (x) = 0
f(x)=0 ⇔ = (x-3) (11x -7) = 0

x-3=0  ou  11x-7=0
x=3 ou x=7\11

s={3 , 7\11}